Phase shifts of the PDO and AMO alter the translation distance of global tropical cyclones - Wang, L; Gu, X; Slater, LJ; Li, J; Kong, D; Zhang, X; Liu, J (Wiley, 2023)
Recent decadal changes in tropical cyclone (TC) frequency since the mid-1990s have been widely reported; however, it is unclear whether there have also been any changes in TC translation distance. Here, we show that long-term decrease in global TC translation distance during 1975–2020 is caused by an abrupt change point around the year 1997. This change point marks a switch between an increasing translation distance during 1975–1997 and decreasing translation distance during 1998–2020. The shift in TC translation distance is attributed to changes in the distance between the location of TC genesis and land, and the percentage of landfalling TCs to all TCs, which is driven by the Pacific Decadal Oscillation (PDO) and Atlantic Multidecadal Oscillation (AMO) phase switch in the mid-1990s. In the last 20 years, the cool, La Niña-like sea surface temperatures (SST) during the PDO negative phase and the warm SST pattern during the AMO positive phase have enhanced the genesis potential index and the potential intensity in offshore areas, resulting in greater TC genesis landward. Phase shifts of PDO and AMO modulate environmental conditions, regulating TC genesis location and landfall frequency, and their combined effects on the translation distance of Pacific TCs. The warm SST anomalies during the AMO positive phase enhance these circulation patterns in two possible ways: via the Indian Ocean and the subtropical eastern Pacific relaying effects at a multidecadal timescale. Our findings suggest that the PDO and AMO act as key pacemakers for decadal changes in global TC translation distance.